Security in work after Covid-19 pandemic - Kasim Mansur; Khairul Hanim Pazim@Fadzim (2021)
Job security is the probability that an individual will keep their job; a job with a high level of security is such that a person with the job would have a small chance of losing it. According to Workmonitor Mobility Index by Randstad Malaysia more Malaysians being worried about their job security — rising to 13% from 6% in the past year. Higher job insecurity facing workers during a pandemic – such as fear of losing permanent job, fear of not getting a job, financial concern and lack of digital skills.